The Place of the Subject in Media Socialization: Between Reception and Virtual Participation - Sola-Morales, S (UNIV CATOLICA URUGUAY, FAC CIENCIAS HUMANAS, 2016)
The aim of this article is to reflect on the socializing condition that media have in a context in which coexist the traditional reception and new forms of virtual participation. Taking as starting point the contributions of Alfred Schutz, Albert Bandura, Claudio Esteva Fabregat and Lluis Duch it is evident the need to deepen the concept of media socialization and the key role of subjects. Therefore, it is necessary to adopt a dialectical perspective that integrates the role of humans as mediators and the socializing capacity of media discourses, leaving behind all passive vision of subjects.